Two new species of Diaphorocleidus and new data on D. affinis (Monogenoidea: Dactylogyridae) parasitizing Bryconops cf. affinis (Characiformes: Iguanodectidae) from the Munim River basin, State of Maranhão, northeastern Brazil - Silva, Marciara Lopes; Cohen, Simone Chinicz; Ottoni, Felipe Polivanov; Viana, Diego Carvalho; Meneses, Yuri Costa De; Justo, Marcia Cristina Nascimento (Zootaxa, 2024)
During a study conducted on the helminth fauna of fishes in the middle Munim River basin, State of Maranhão, northeastern Brazil, three species (two new) of Diaphorocleidus Jogunoori, Kritsky & Venkatanarasaiah, 2004 are reported from the gills of the “piaba” Bryconops cf. affinis (Iguanodectidae): Diaphorocleidus affinis (Mizelle, Kritsky & Crane, 1968), D. forcipiformis n. sp. and D. munimensis n. sp. New morphological data, drawings, and geographic distribution were provided for D. affinis. Diaphorocleidus forcipiformis n. sp. is characterized by a male copulatory organ with 2½ rings counterclockwise and base forming a small tube with two circular flanges and accessory piece bifurcated, claw-shaped, with parts similar in shape and size, one of them distally bifid. Diaphorocleidus munimensis n. sp. is differentiated by the accessory piece, which is composed of two large pieces, united in their proximal part, claw-shaped, and distally hooked. The findings of this initial survey on the helminth parasites of fishes in this area emphasize the importance of carrying out comparable surveys on other fish species. Such surveys may lead to the identification of unknown species or new occurrences.